PILAR-PILAR PENDIDIKAN ISLAM DI KESULTANAN ACEH - Iswandi Iswandi (Edudeena : Journal of Islamic Religious Education, 2019)
Abstract: Talking about Islamic education in Aceh means that it will be confronted with the embryos of Islamic education in the archipelago. The Perlak Kingdom which was founded in 840 AD was the first Islamic kingdom. Arab influence is very strong in the development of Islam in Aceh, especially during the reign of the Caliph of the Abbasids. Some Islamic educational institutions in the Sultanate of Aceh are Meunasah which are traditional educational institutions and become basic education institutions in every village in Aceh. In the learning process, meunasah teaches about the basics of Islamic education. Rangkang is a secondary education institution and is a continuation of the meunasah. For students who want to continue their education to dayah, then he must attend education in the arena. In its journey, the framework is also called middle-level dayah education. Dayah is also referred to as a higher education institution in Aceh, because what is taught is adults and already have knowledge about Islam. Dayah education covers two levels: i.e. intermediate level and high level. Middle level dayah education is called fram and high level education is called bale. Whereas the most influential cleric was Hamzah Fansuri who was famous for his poems Samsuddin Sumatrani who had an important role in the Sultanate of Aceh. Nuruddin ar-Raniri, a follower of the Rifa'iyah order he obtained through Ba Syaiban, obtained this tarekat from his teacher Sheikh Muhamad al-Aidarusi, the spiritual grandfather of ar-Raniri Abdurrauf Singkel, he was also known as the Syiah Kuala or Teungku in Kuala. Abstrak: Berbicara tentang pendidikan Islam di Aceh berarti akan dihadapkan dengan embrio pendidikan Islam di nusantara. Kerajaan Perlak yang didirikan pada 840 M adalah kerajaan Islam pertama. Pengaruh Arab sangat kuat dalam perkembangan Islam di Aceh, terutama pada masa pemerintahan Khalifah Abbasiyah. Beberapa lembaga pendidikan Islam di Kesultanan Aceh adalah Meunasah yang merupakan lembaga pendidikan tradisional dan menjadi lembaga pendidikan dasar di setiap desa di Aceh. Dalam proses belajarnya, meunasah mengajarkan tentang dasar-dasar pendidikan Islam. Rangkang adalah lembaga pendidikan menengah dan merupakan kelanjutan dari meunasah. Bagi siswa yang ingin melanjutkan pendidikan ke dayah, maka ia harus menghadiri pendidikan di arena. Dalam perjalanannya, kerangka kerja ini juga disebut pendidikan dayah tingkat menengah. Dayah juga disebut sebagai lembaga pendidikan tinggi di Aceh, karena yang diajarkan adalah orang dewasa dan sudah memiliki pengetahuan tentang Islam. Pendidikan Dayah mencakup dua tingkat: yaitu tingkat menengah dan tingkat tinggi. Pendidikan dayah tingkat menengah disebut fram dan pendidikan tingkat tinggi disebut bale. Sedangkan ulama yang paling berpengaruh adalah Hamzah Fansuri yang terkenal dengan puisinya Samsuddin Sumatrani yang memiliki peran penting dalam Kesultanan Aceh. Nuruddin ar-Raniri, pengikut ordo Rifa’iyah yang ia peroleh melalui Ba Syaiban, memperoleh tarekat ini dari gurunya Sheikh Muhamad al-Aidarusi, kakek spiritual ar-Raniri Abdurrauf Singkel, ia juga dikenal sebagai Syiah Kuala atau Teungku di Kuala.